Quo Vadis, development communication? thoughts on the practice of devcom in a knowkedge - Librero, Felix (2008)
These are some of my deeper thoughts and concerns about development communication as I have lived it as a profession and calling. I also discuss the current challenges that development communicators are facing as I see it, and finally, I give a bird's eye-view of the directions we most likely are going to take in the next decade - all these from my own personal perspective. This may mean that I will, now and then, digress from the standard academic approach to the discussion of development communication. What I wish to share is not much how we teach development communication as much how I have applied and lived it. This presentation, therefore, is a personal account rather than an academic presentation. It is my belief that this is a more meaningful way of explaining how I got involved in development communication.